The potential of the metabolites active from Moringa leaves (Moringa oleifera, Lam) on sensitivity of doxorubicin towards breast cancer: in silico studies - FRENGKI FRENGKI; KMS M AMIN ALQADRI; SITI AISYAH; HENNIVANDA HENNIVANDA (Universitas Syiah Kuala, 2023)
Breast cancer is one type of cancer with the highest incidence suffered by women. Doxorubicin is a chemotherapy that is often used as the main chemotherapy and combination chemotherapy, but the use of doxorubicin is often complained of side effects that cause auto resistance. Combination with chemopreventives from natural ingredients has become an option to increase therapeutic response and to minimize side effects and resistance to chemotherapy use. This study aims to screen several active compounds of the phenolic-flavonoid group contained in Moringa leaves (Moringa oleifera, Lam) against NFκβ receptors in silico using a molecular docking technique. The material in the form of “Canonical smiles” data is quercetin, quercetin-3 glycoside (Q3G), rutin, kaempferol, myricetin, isorhamnetin, deoxyelephantopin and doxorubicin which were downloaded from www.pubchem.org and converted to 3D structures using MOE software. While the 3D structure of the receptor (1VKX) was downloaded from www.rscb.org. The results of the docking of the active compounds contained in Moringa leaves (Moringa oleifera, Lam) showed a fairly strong affinity by releasing energy when forming a ligand-receptor complex. Quercetin 3-glycoside has the best potential as an NF inhibitor with an affinity of -14.23 kcal/mol. Quercetin 3-glycoside also has a good pharmacokinetic profile with low toxicity. While the phenolic-flavonoid compounds contained in other Moringa leaves are only able to reduce the affinity of doxorubicin for the NF receptor by changing the